Psychological capital and job search: A systematic literature review and agenda for future research - María-Magdalena Fernández-Valera (International Journal for Research in Vocational Education and Training (IJRVET), 2023)
Purpose: There is consistent evidence that a positive mindset could foster the job search process. Psychological capital, defined as a tendency to hold cognitions and positive appraisals of one's ability, could highlight the importance of individual cognitive appraisal in the job search process. Nevertheless, psychological capital's impact on job seekers is still unclear. Methods: The purpose of the present study was to explore the role of psychological capital in the job search process. The author conducted a systematic review following the PRISMA-P guidelines. This systematic review sought answers to three questions: 1) What theories are applied to explain the relationship between psychological capital and the job search process? 2) How is the association between psychological capital and the job search process? 3) Did the psychological capital interventions positively influence the job search process? The review focused on quantitative studies carried out between 2007 and 2021 on job seekers. Finally, 11 studies fit the inclusion criteria. Results: Overall, the literature review supports the significant association between psychological capital and the job search process. On the one hand, the studies analyzed have shown the resonance of psychological capital on the job search outcomes and job seekers' well-being. On the other hand, the results showed insufficient evidence to make any firm conclusions concerning psychological capital interventions' effects on the job search process improvement. Conclusion: It is concluded that psychological capital may be a valuable advantage for helping job seekers engage in their job search process. The results presented in this study could have important implications for job seekers and public and private employment agencies. Even so, it is necessary to continue contributing to its development. Particularly, there is still considerable scope for improvement in the study of psychological capital and the job search process in terms of the study design we apply, the variables we study and their measure, and the theoretical background we use to explain the previous relationship.
urn:nbn:de:gbv:18-10-1103-6
Keywords: 330; Psychological Capital; Job Search; Unemployment; Job Seekers; VET; Vocational Education and Training